RNA N6‐methyladenosine methyltransferase‐like 3 promotes liver cancer progression through YTHDF2‐dependent posttranscriptional silencing of SOCS2 - Chen, Mengnuo; Wei, Lai; Law, Cheuk‐Ting; Tsang, Felice Ho‐Ching; Shen, Jialing; Cheng, Carol Lai‐Hung; Tsang, Long‐Hin; Ho, Daniel Wai‐Hung; Chiu, David Kung‐Chun; Lee, Joyce Man‐Fong; Wong, Carmen Chak‐Lui; Ng, Irene Oi‐Lin; et al. (Hepatology (Baltimore, Md.), 2018)
Epigenetic alterations have contributed greatly to human carcinogenesis. Conventional epigenetic studies have predominantly focused on DNA methylation, histone modifications, and chromatin remodeling. Recently, diverse and reversible chemical modifications of RNAs have emerged as a new layer of epigenetic regulation. N6‐methyladenosine (m6A) is the most abundant chemical modification of eukaryotic messenger RNA (mRNA) and is important for the regulation of mRNA stability, splicing, and translation. Using transcriptome sequencing, we discovered that methyltransferase‐like 3 (METTL3), a major RNA N6‐adenosine methyltransferase, was significantly up‐regulated in human hepatocellular carcinoma (HCC) and multiple solid tumors. Clinically, overexpression of METTL3 is associated with poor prognosis of patients with HCC. Functionally, we proved that knockdown of METTL3 drastically reduced HCC cell proliferation, migration, and colony formation in vitro. Knockout of METTL3 remarkably suppressed HCC tumorigenicity and lung metastasis in vivo. On the other hand, using the CRISPR/dCas9‐VP64 activation system, we demonstrated that overexpression of METTL3 significantly promoted HCC growth both in vitro and in vivo. Through transcriptome sequencing, m6A sequencing, and m6A methylated RNA immuno‐precipitation quantitative reverse‐transcription polymerase chain reaction, we identified suppressor of cytokine signaling 2 (SOCS2) as a target of METTL3‐mediated m6A modification. Knockdown of METTL3 substantially abolished SOCS2 mRNA m6A modification and augmented SOCS2 mRNA expression. We also showed that m6A‐mediated SOCS2 mRNA degradation relied on the m6A reader protein YTHDF2‐dependent pathway. Conclusion: METTL3 is frequently up‐regulated in human HCC and contributes to HCC progression. METTL3 represses SOCS2 expression in HCC through an m6A‐YTHDF2‐dependent mechanism. Our findings suggest an important mechanism of epigenetic alteration in liver carcinogenesis. (Hepatology 2018;67:2254‐2270).